Integrating genetic and clinical data to predict impulse control disorders in Parkinson's disease. (9th November 2020) - Jesús, S.; Periñán, M. T.; Cortés, C.; Buiza‐Rueda, D.; Macías‐García, D.; Adarmes, A.; Muñoz‐Delgado, L.; Labrador‐Espinosa, M. Á.; Tejera‐Parrado, C.; Gómez‐Garre, M. P.; Mir, P.
Abstract : Background and purpose: Impulse control disorders (ICDs) are frequent in Parkinson's disease (PD), with associated clinical and genetic risk factors. This study was aimed at analyzing the clinical features and the genetic background that underlie ICDs in PD. Methods: We included 353 patients with PD in this study (58.9% men, mean age 62.4 ± 10.58 years, mean age at disease onset 52.71 ± 11.94 years). We used the validated Questionnaire for Impulsive–Compulsive Disorders in Parkinson's Disease for ICDs screening. Motor, nonmotor, and treatment‐related features were evaluated according to the presence of ICDs. Twenty‐one variants related to dopaminergic, serotonergic, glutamatergic, and opioid neurotransmitter systems were assessed. Association studies between polymorphisms and ICDs were performed. The combination of clinical and genetic variables was analyzed with receiver operating characteristic curves to assess the predictability of experiencing ICDs. Results: Impulse control disorders appeared in 25.1% of the cases. Patients with ICDs were younger and presented a higher rate of anxiety. Treatment with dopamine agonists increased the risk of ICDs and it was dose dependent ( P  < 0.05). Genetic association studies showed that the DOPA decarboxylase gene ( DDC ), rs1451375, might modulate the risk of ICDs. Plotting the clinical–genetic model, the predictability of ICDs increased 11% (area under curve = 0.80; z  = 3.22, P  = 0.001) when adding the genotype data for single nucleotide polymorphisms. Conclusions: Polymorphisms in DDC might act as risk markers for ICDs in PD. The predictability of experiencing ICDs increased by adding genetic factors to clinical features. It is therefore important to assess the patient's genetic background to identify individuals at risk for ICDs. Abstract : We studied the clinical features and the genetic background that underline impulse control disorders (ICDs) in 532 Parkinsons's disease (PD) patients. Treatment with dopamine agonists increased the risk of ICDs and it was dose dependent ( P  < 0.05). The DOPA decarboxylase gene ( DDC ) variant, rs1451375, might modulate the risk of ICDs in PD. The predictability of experiencing ICDs increased an 11% by adding genetic factors to clinical features. It is therefore important to assess the patient's genetic background to identify individuals at risk for ICDs.